2017
DOI: 10.1007/s11111-017-0275-1
|View full text |Cite
|
Sign up to set email alerts
|

Family planning and deforestation: evidence from the Ecuadorian Amazon

Abstract: Despite an abundant body of literature exploring the relationship between population growth and forest cover change, comparatively little research has explored the forest cover impacts of family planning use, which is a key determinant of the rate of population growth in many developing country contexts. Using data from a farm-level panel survey in the Northern Ecuadorian Amazon, this paper addresses whether family planning use impacts forest cover change. Longitudinal model results show that after controlling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…New farmers are said to clear more wetland to establish themselves especially wetlands that are regarded as communal lands. [25] and [32] found that higher rates of deforestation occur at early stages of farm settlement. Long cultivation results in declining yields so that an investment in the quality of the land would sustain its productivity, thereby increasing the benefits from the investment, which might encourage farmers to invest.…”
Section: Years Spent In Active Farmingmentioning
confidence: 99%
“…New farmers are said to clear more wetland to establish themselves especially wetlands that are regarded as communal lands. [25] and [32] found that higher rates of deforestation occur at early stages of farm settlement. Long cultivation results in declining yields so that an investment in the quality of the land would sustain its productivity, thereby increasing the benefits from the investment, which might encourage farmers to invest.…”
Section: Years Spent In Active Farmingmentioning
confidence: 99%
“…With more forest available there are more opportunities to deforest and the price of land usually lower. This was confirmed by regional and local studies in Ecuador since the 1980s [66,77,82,110] and in more recent cases in the Brazilian Amazon [89,98,115] and in Madre de Dios, Peru [116]. Farm size was also associated with greater deforestation, but in these cases, it was often due to the higher amount of forest available in those farms, rather than farm size itself being a reason for greater deforestation.…”
Section: Underlying Driversmentioning
confidence: 63%
“…Similarly, many studies across the biome linked forest loss to roads, reflected by a distinctive fish-bone pattern of deforestation. In fact, accessibility to markets via roads was identified as an important underlying driver in the Amazon [74][75][76][77]. Infrastructure thus acts as a twofold driver, both proximate and underlying, and often dictates the pattern of deforestation.…”
Section: ) How Do the Proximate Causes Underlying Drivers And Moderat...mentioning
confidence: 99%
See 2 more Smart Citations